MICRORNA IN MONITORING OF THE EVOLUTION OF GLIAL CEREBRAL TUMORS - R. Yu. Seliverstov; M. I. Zaraiskiy; R. V. Tyurin; A. G. Naryshkin; V. G. Valerko; V. V. Semiglazov; Ch. Takahachi (Сибирский онкологический журнал)
Glial cerebral tumors (GCT) are primary tumors of the central nervous system that develop from glial tissue. Despite the use of combination treatment, the overall median survival rate in patients with glioblastoma, the most malignant form of HCC, is low. MicroRNA is a large class of endogenous small RNA molecules that inhibit mRNA translation of target genes involved in the evolution of GCT. It was shown that miRNA-21 has antiapoptotic and invasive functions by means of silencing of the PTEN tumor suppressor. MicroRNA-128 can activate a number of genes that are responsible for the mechanisms of suppression of tumor growth. MicroRNA-342, modulating PAK4 gene expression, is involved in the control of tumor cell proliferation, invasion and apoptosis.The aim of the work was to study the feasibility of using the assessment of miRNA-21, -128 and -342 expressions in the blood plasma and saliva of patients to monitor GCT progression or stabilization during combined modality treatment.Material and Methods. The main group consisted of 56 patients with GCTs. (34 men and 22 women), aged 25 to 72 years (average age 48.5 years) GCTs. The control group consisted of 50 people (45 volunteers and 5 neurosurgical patients with extracerebral meningiomas). The study of miRNA-21, -128, and -342 expressions was carried out according to the semiquantitative StemLoopRealTime protocol, using small U6 RNA as a reference gene. Data was processed using the STATISTICA for Windows computer system.Results. In 70 % of patients with disease progression assessed by magnetic resonance imaging, without progression in cerebral and focal neurological signs, the expression level of miRNA21 exceeded the control values both in blood plasma and saliva, and the expression levels of miRNA-128 and -342 were significantly reduced. In patients with GCT stabilization, the expression levels of miRNA-21, -128, and -342 did not go beyond the reference values. The diagnostic significance of miRNA-128, -342 for GCT was 69 %; therefore these miRNAs can be used in a clinical setting. Thus, the increased expression of miRNA-21 and decreased expressions of miRNA-128 and -342 in both blood plasma and saliva indicate cerebral glioma progression.